Case Report: A myasthenia gravis patient complicated with renal failure was effectively treated with efgartigimod - Ke, Jia; Zhao, Qi; Wang, Na; Zhang, Bei; Hu, Jin-Quan (Frontiers in Immunology, 2025)
Myasthenia gravis (MG) is a neuromuscular junction disorder clinically characterized by fluctuating muscle weakness, in which some patients with respiratory muscle weakness are at risk of progressing to myasthenia gravis crisis and respiratory failure, requiring treatment with rapid antibody clearance. Currently widely used intravenous immunoglobulin and plasma exchange therapy remains ineffective in some patients and is limited by multiple contraindications. Efgartigimod is a newly approved FcRn antagonist for the treatment of myasthenia gravis, which rapidly cleans IgG antibodies in the body, but there is still a lack of guidance on the use of efgartigimod in patients with renal insufficiency. Here, we report a case of MG patient with end-stage renal disease undergoing maintenance hemodialysis who successfully navigated a myasthenic crisis and achieved significant clinical remission through efgartigimod therapy. Moreover, sustained efgartigimod maintenance therapy enabled achievement of clinical minimum state. This case demonstrates the therapeutic potential of efgartigimod in MG patients with concomitant renal impairment and provides clinical evidence supporting its application in this special population.